2009
DOI: 10.1159/000212504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inbreeding on the Distribution of Compound Heterozygotes: A Lesson from Lipase H Mutations in Autosomal Recessive Woolly Hair/Hypotrichosis

Abstract: Autozygosity mapping in consanguineous families has proven to be a powerful method for identifying recessive disease genes. Using this technique with whole genome SNP data generated from low density mapping arrays, we previously identified two genes that underlie autosomal recessive woolly hair (ARWH/hypotrichosis; OMIM278150), specifically P2RY5 and Lipase H (LIPH). In the current study, we sought to identify a novel disease locus for ARWH/hypotrichosis by analyzing two large consanguineous families from Paki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…So far, 14 LIPH gene mutations have been reported, four of which are prevalent Horev et al, 2009;Jelani et al, 2008;Kamran-ul-Hassan Naqvi et al, 2009;Kazantseva et al, 2006;Nahum et al, 2009;Naz et al, 2009;Pasternack et al, 2009;Petukhova et al, 2009;Shimomura et al, 2009a,b,c]. One prevalent mutation, 985-bp deletion including exon 4 and the flanking introns, was detected in a large number of ARH patients from two ethnic groups, the Chuvash and Mari, in the Volga-Ural region of Russia [Kazantseva et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, 14 LIPH gene mutations have been reported, four of which are prevalent Horev et al, 2009;Jelani et al, 2008;Kamran-ul-Hassan Naqvi et al, 2009;Kazantseva et al, 2006;Nahum et al, 2009;Naz et al, 2009;Pasternack et al, 2009;Petukhova et al, 2009;Shimomura et al, 2009a,b,c]. One prevalent mutation, 985-bp deletion including exon 4 and the flanking introns, was detected in a large number of ARH patients from two ethnic groups, the Chuvash and Mari, in the Volga-Ural region of Russia [Kazantseva et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…A deletion mutation exon7_8del has been identified in five consanguineous Pakistani families and 1 Guyanese family [Jelani et al, 2008;Petukhova et al, 2009;Shimomura et al, 2009bShimomura et al, , 2009c. A small deletion mutation 659_660delTA has been identified in several consanguineous Pakistani families and 1 Guyanese family [Jelani et al, 2008;Petukhova et al, 2009;Shimomura et al, 2009b,c].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although homozygous muta- tions are a common cause of disease in consanguineous families, it also happens regularly that consanguinity is unrelated to the disorder. Thus, compound heterozygosity can be causative for recessive genetic disorders and one should be aware of this, particularly when studying outbred families or families with affected individuals residing in a single sibship [84,85] .…”
Section: Homozygosity Mappingmentioning
confidence: 99%
“…A recent study has explored the relationship between allele frequencies, the inbreeding coefficient, the number of mutations segregating and the probability that an individual affected with a recessive disorder is a compound heterozygote (Petukhova et al 2009). The authors concluded that compound heterozygosity underlies disease in A.…”
Section: Introductionmentioning
confidence: 99%